211 Overcoming the Growth Deficits Programmed by Maternofetal Stress. (21st September 2022) - Yates, Dustin T
Abstract: Prolonged maternofetal stress stunts placental development and causes fetal programming that reduces fetal growth and birthweight. Low birthweight due to intrauterine growth restriction (IUGR) of the fetus increases perinatal mortality. More commonly, however, it results in lifelong impairment of muscle growth capacity and metabolic function. In humans, low birthweight increases risk for obesity, diabetes, and other metabolic disorders by an estimated 18-fold. Similarly, low birthweight livestock exhibit greater early death loss, poor growth efficiency, and lower-quality carcasses at harvest. These animals manifest poor feed-to-gain ratios, less lean mass, and greater fat deposition. Together, these outcomes increase production costs, decrease value, and reduce the amount of meat produced per animal. The fetal programming mechanisms linking stress induced IUGR to impaired postnatal growth and metabolic efficiency are largely unknown. However, recent findings in IUGR fetal and neonatal lambs produced experimentally by maternal heat stress and maternofetal inflammation (and pair-fed controls) indicated skeletal muscle-centric programming of adrenergic and inflammatory pathways. Specifically, studies found reduced β2 adrenergic tone and enriched inflammatory signaling pathways. These changes coincided with intrinsic myoblast dysfunction, reduced muscle fiber hypertrophy, and impaired skeletal muscle glucose metabolism. Additionally, IUGR fetal and neonatal lambs exhibited impaired β cell function that may also be associated with adrenergic and inflammatory programming. Subsequent studies have investigated these mechanisms as potential therapeutic targets for interventions and treatments, which is a fundamental step in developing strategies to improve outcomes in low birthweight humans and livestock.